(untitled) (Bangladesh Journal of Physics, 2023)
(1-x)BaTiO3+xCu0.1Co0.9Fe2O4;(x=0.0,0.1,0.3,0.5,1.0) multiferroic composites were being prepared by conventional solid-state reaction process. The structure and microstructure of the prepared samples was detected by the X-ray diffractometer. The X-ray diffraction analysis confirmed the tetragonal structure for x=0.0, cubic structure for x=0.1, 0.3, 0.5 and cubic spinel structure for x=1.0. Morphological analyses were carried out by the Scanning Electron Microscope (SEM). Surface morphology confirmed that the grain size and porosity decrease with the increment of ferrite content. Magnetic properties of the prepared samples were determined by Vibrating Sample Magnetometer (VSM). The magnetic saturation (Ms) was found to increase with increasing spinel content. Dielectric constant ( ), complex permeability (m′), DC and AC resistivity of the composites were determined by an impedance analyzer. The dielectric constant shows dispersive behavior in the low frequency region and was frequency independent in high frequency range. Dielectric constant decreases with increasing ferrite content whereas complex permeability increases. Lower value of loss factor and higher value of relative quality factor (RQF) was obtained. Activation energy of the samples was calculated from DC resistivity which confirmed the shifting from conducting nature to semiconducting nature. Bangladesh Journal of Physics, Vol. 30, Issue 1, pp. 43–56, June 2023